Experimental and Numerical Evaluation of Mechanical Properties for Carbon Fiber Reinforced Epoxy LY5052 Composite for Prosthesis Structures - Mahfud Ibadi; Yudan Whulanza; Herry Purnomo; David N Vicarneltor; Tresna P Soemardi; Gatot Prayogo (Jurnal Teknik Mesin, 2022)
Carbon Fiber Reinforced Epoxy is a material that is widely used in the manufacture of prosthesis structures. In this research, the carbon fiber used is plain weave-type carbon, while the matrix used is LY5052 epoxy, LY5052 epoxy has advantages such as low viscosity and long pot life making it possible to manufacture large-sized prostheses. The first step in this research is making specimens using the vacuum infusion method and then cutting the specimens with dimensions referring to ASTM D3039. Furthermore, tensile test experiments were carried out with the results obtained that the maximum stress () was 537.15 MPa. As an evaluation, a tensile test simulation was carried out with Finite element analysis using Abaqus software, the material properties used were the results of a tensile test experiment, in the process the mesh selection was carried out by input sizing control many times this was done to determine the accuracy of the results. The tensile test simulation results with abaqus software are 523.3 MPa when compared to the experimental, the difference is only 2.58%. based on experimental and simulation results, the mechanical properties of the Carbon Fiber Reinforced Epoxy LY5052 Composite material are almost the same, so that in the manufacture of prosthesis the mechanical properties data in this study can be used when performing numerical analysis in the prosthesis design process.